Application of Digital Literature Analysis in Analyzing The Relationship Between Schools' Ability in Updating The Curriculum and Students' Readiness to Face Challenges in The Era of Digitalization - Isna Juwita; Anastasia D'Ornay; Fransisca Jallie Pattiruhu; Caka Gatot Priambodo; Heri Satria Setiawan (SEULANGA SYSTEM PUBLISHER, 2024)
This research aims to determine the conditions of educational and pedagogical reform. The methodology used is qualitative. Researchers used a qualitative approach, including historical source analysis instruments, content analysis, participant and non-participant observation, and interviews. The research reveals each center's uniqueness and educational identity, examining its internal organization, approach, relationship with the environment, participation models, and other aspects. This shows that there is room for various educational strategies and models that can improve the quality of learning. Daily educational activities reveal elements of traditional pedagogical culture, including textbooks as the primary work material, minimal parental participation, and classes dominated by conventional pedagogical relationship methods. On the other hand, these schools exhibit extraordinary dynamism and unlimited pluralism in their pedagogical reforms. The various networks, teacher collectives, and other initiatives reflect this, striving to renew and reaffirm the approaches of the new school movement while also demonstrating the collective crystallization of the claims that form the foundation of the critical subject. Finally, national and international reports have shown the importance of carefully reflecting on the pedagogical conclusions drawn in education. These conclusions can provide valuable insight into the direction and efforts that should be made to improve the education system as a whole.